STEM 4.0 APPROACH TO STRENGTHEN ADAPTIVE STUDENT CHARACTER - Ismu Sukamto; Hervin Maulina; Deviyanti Pangestu; Anik Ghufron (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The purpose of this study was to determine the effectiveness of the STEM 4.0 approach in increasing CT which included differences in CT in experimental and control class students and in increasing student CT.The research method used is Quasi-Experimental Design with One Group Pretest-Postest. This research involved 56 university students. The sample was treated in the form of learning with the STEM approach. Student CT includes 5 indicators, namely: (1) Interpreting Problems, (2) Analyzing Solution of the Problem, (3) Applying Gained Solution, (4) Evaluating the Gained Solution, and (5) Concluding the Results Attached with Supportive Evidence.The results of the study prove that based on the results of the Independent T-Test, there are significant differences in students' CT in the STEM class and the conventional class. The increase in CT in the experimental group was also significant based on the results of the Paired Samples Test. Thus, it can be concluded that the STEM 4.0 approach facilitates students to master the concepts of learning materials (Science) with the help of technology (Technology) and is strengthened by the application of these concepts in making simple products (Engineering). In addition, concept mastery is also supported by linking environmental phenomena in learning (Mathematics). The implementation of STEM 4.0 is effective in improving CT.